The complex phenotype and function of spinal cord microglia during ALS progression and the impact of metabotropic glutamate receptor type 5 down-regulation in SOD1G93A mice - Matilde Balbi; Carola Torazza; Tiziana Altosole; Silvia Ravera; Emanuele Farinini; Sara Tessitore; Francesca Bacchetti; Francesca Rosso; Ilaria Musante; Silvana Alfei; Maria Cerminara; Aldamaria Puliti; et al. (Neurobiology of Disease, 2025)
Over the last few decades, scientists' attention has shifted from neuronal to non-neuronal cells to explain the mechanisms at the basis of neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS). ALS is a multifactorial and multicellular disease in which microglia have a central role, during disease progression. We previously demonstrated that metabotropic glutamate receptor 5 (mGluR5) is dysfunctional in the spinal cord of the SOD1G93A ALS mice, and its in-vivo genetic or pharmacological dampening ameliorates disease outcome and astrocyte and microglia reactivity. Here, we studied the expression of typical phenotype-related markers during the disease progression in spinal cord microglia cells acutely isolated from early asymptomatic and late symptomatic SOD1G93A ALS mice. Moreover, we investigated whether reducing mGluR5 affected the microglia phenotype and function. In contrast to what we previously observed in astrocytes, mGluR5 expression decreased during disease progression in microglia acutely isolated from adult SOD1G93A mice. In-vivo genetic mGluR5 downregulation did not affect microglia phenotype-relevant markers, which evidenced a unique expression distribution. Conversely, mGluR5 reduction ameliorated redox balance and bioenergetics of adult microglia. Microglia cultured from the spinal cord of SOD1G93A pups showed that in-vitro mGluR5 pharmacological manipulation by the negative allosteric modulator CTEP partially modified their bioenergetic and oxidative status. Overall, our results suggest that mGluR5 manipulation ameliorates microglia phenotype and function in ALS by both direct and indirect mechanisms. Consequently, we hypothesised that the improvement of microglia reactive status by in-vivo mGluR5 downregulation or CTEP pharmacological modulation is supported by ameliorated bioenergetic metabolism, and the indirect astrocyte's phenotype change that promotes an improvement of the surrounding environment.